Job satisfaction towards employees performance among staff in Small District Office Gemas / Masanie Abd Ghani and Maslizah Khamis - Abd Ghani, Masanie; Khamis, Maslizah (Faculty of Business and Management, 2013)
This research is to determine the relationship between the job satisfaction and employees performance in the Small District Office Gemas. Four factor that effect employees job satisfaction are salaries, bonuses, work environment and work experiences, are the independent variable while job satisfaction towards employees performance among staff in the Small District Office Gemas as the dependent variable. Each of the factors was tested to see the correlation between each factors and the dependent variable. The factor also was tested by using level of mean to see the bigger impact of independent variable with the dependent variable. Questionnaire method has been used in this research. 32 respondents among staff in the Small District Office Gemas participated in this survey. The significant of each independent variable to the dependent variable has been test by using the analysis of pearson correlation coefficient. Only work experiences show the relationship between independent variable and dependent variable. Besides that, the bigger impact of independent variable with the dependent variable has been test by using the level of mean. From the result, work environment show the higher value with 4.0625. Only salaries show the moderate result and the other factors of independence variable are high.